Reshaping the Heart-Mind: A Response to Rowan Williams - Teasdale, John D. (Zygon, 2023)
This article suggests that themes in Williams' (2023) analysis of attention and contemplation resonate powerfully with current thinking in cognitive science. By changing how we pay attention, we can change the shape, or underlying configuration, of the heart-mind. This is the core process in mindfulness and contemplation. The Interacting Cognitive Subsystems (ICS) analysis suggests this involves a shift in the balance between conceptual knowing and holistic-intuitive knowing.